2009
DOI: 10.1677/jme-08-0162
|View full text |Cite
|
Sign up to set email alerts
|

The clinical–molecular interface of somatostatin, dopamine and their receptors in pituitary pathophysiology

Abstract: The role of somatostatin and dopamine receptors as molecular targets for the treatment of patients with pituitary adenomas is well established. Indeed, dopamine and somatostatin receptor agonists are considered milestones for the medical therapy of these tumours. However, in recent years, the knowledge of the expression of subtypes of somatostatin and dopamine receptors in pituitary adenomas, as well as of the coexpression of both types of receptors in tumour cells, has increased considerably. Moreover, recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
59
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 76 publications
0
59
0
3
Order By: Relevance
“…Behavioral and clinical evidence in brain research indicated an interaction between the somatostatinergic and dopaminergic systems (Chneiweiss et al 1985, Martin-Iverson et al 1986, Izquierdo-Claros et al 1997, Marzullo et al 1999, recently confirmed by in vitro studies (Rocheville et al 2000a, Baragli et al 2007, Kidd et al 2008. It is well known that SSTR and DR are widely expressed both in normal human neuroendocrine tissues and in tumors (Reubi et al 1987, Pivonello et al 2007b, such as pituitary adenomas (Stefaneanu et al 2001, Moller et al 2003, Saveanu et al 2008, Ferone et al 2009) and adrenal tumors (Pivonello et al 2007a,b, de Bruin et al 2009a. Since SSTR and D 2 -like receptors mainly exert inhibitory functions, medical therapies targeting these receptors with selective agonists have been developed for the treatment of a number of neuroendocrine disorders.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Behavioral and clinical evidence in brain research indicated an interaction between the somatostatinergic and dopaminergic systems (Chneiweiss et al 1985, Martin-Iverson et al 1986, Izquierdo-Claros et al 1997, Marzullo et al 1999, recently confirmed by in vitro studies (Rocheville et al 2000a, Baragli et al 2007, Kidd et al 2008. It is well known that SSTR and DR are widely expressed both in normal human neuroendocrine tissues and in tumors (Reubi et al 1987, Pivonello et al 2007b, such as pituitary adenomas (Stefaneanu et al 2001, Moller et al 2003, Saveanu et al 2008, Ferone et al 2009) and adrenal tumors (Pivonello et al 2007a,b, de Bruin et al 2009a. Since SSTR and D 2 -like receptors mainly exert inhibitory functions, medical therapies targeting these receptors with selective agonists have been developed for the treatment of a number of neuroendocrine disorders.…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, somatostatin (SS) and dopamine (DA) receptors have been highlighted as two critical regulators involved in the negative control of hormonal secretion in a wide group of neuroendocrine tumors (NET), including pituitary adenomas (Ben-Jonathan & Hnasko 2001, Guillemin 2005, Ferone et al 2009). Moreover, SS, DA, and their receptors represent two major systems that share a number of structural and functional characteristics (Rocheville et al 2000a, Baragli et al 2007, Srirajaskanthan et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of other DA, like bromocriptine, is probably lower than that of cabergoline (4). These two drug classes (SA and DA) act on somatotropinoma through binding to its receptors (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, its negative effects on glucose tolerance are even more pronounced than with Octreotide (14,20). On the other hand, BIM-23A760 (Dopastatin), a chimeric molecule directed towards somatostatin (mainly sst2 and sst5) and dopamine D2 receptors (21,22,23), suppresses GH in vitro but was ineffective when applied to acromegalic patients in clinical trials (press release 15 Dec 2010, Ipsen Pharma).…”
Section: Introductionmentioning
confidence: 99%